iTRAQ and PRM-Based Proteomic Analysis Provides New Insights into Mechanisms of Response to Triple Therapy in Patients with Rheumatoid Arthritis - Chen J; Li S; Ge Y; Kang J; Liao JF; Du JF; Tian J; Xie X; Li F (Dove Medical Press, 2021)
Jian Chen, Shu Li, Yan Ge, Jin Kang, Jia-fen Liao, Jin-feng Du, Jing Tian, Xi Xie, Fen Li Department of Rheumatology and Immunology, The Second Xiangya Hospital of Central South University, Changsha, Hunan, People's Republic of ChinaCorrespondence: Fen LiDepartment of Rheumatology and Immunology, The Second Xiangya Hospital of Central South University, No. 139 Ren Min Middle Road, Changsha, 410011, People's Republic of ChinaEmail lifen0731@csu.edu.cnBackground: Approximately 30% of patients with rheumatoid arthritis (RA) respond poorly to combination therapy of multiple drugs. The molecular mechanisms of different responses to methotrexate + leflunomide + infliximab therapy in patients with RA were explored in this study.Methods: Infliximab was administered to patients with RA whose disease activity score was higher than 5.1 after 1 month of combination therapy with methotrexate and leflunomide. After 14 weeks of undergoing triple therapy, patients with RA were classified as responders and non-responders. Protein profiles at baseline and 14th week were investigated via isobaric tags for relative and absolute quantification (iTRAQ), and proteins with significant differences ≥ 1.2 folds change or ≤ 0.8 folds change were defined as differentially expressed proteins (DEPs). Overlapping DEPs between responders and non-responders were confirmed by parallel reaction monitoring (PRM). Bioinformatic analyses were performed for DEPs.Results: The results revealed 5 non-responders (NRs) and 15 responders (Rs). iTRAQ analysis indicated 13 overlapping DEPs and included 6 opposite change DEPs such as testicular tissue protein Li 70, cofilin 1, fibrinogen beta chain, galectin-10, serotransferrin (TF) and albumin. The difference in serotransferrin between responders and non-responders confirmed by PRM was significant. Verification by PRM indicated that TF was elevated in the Rs group and was reduced in the NRs group. Bioinformatic analysis indicated that serotransferrin was involved in the hypoxia-inducible factor-1 pathway and ferroptosis.Conclusion: Serotransferrin-related molecular mechanism may be a new direction to study refractory RA.Keywords: rheumatoid arthritis, proteomics, effectiveness, disease modifying antirheumatic drugs, serotransferrin